(untitled) (World Science, 2021)
The paper proposes, based on the method of precedents, a conceptual model of precedent formation of the portfolio of logistics service providers in projects of formation and implementation of logistics outsourcing strategy, which is considered as an evolving strategy. This model can be used as a basis for developing methodological aspects of content management of these projects.